PELAKSANAAN PENANGANAN PENYIDIKAN TINDAK PIDANA PERSETUBUHAN DAN PENCABULAN TERHADAP ANAK DI POLSEK EMPAT ANGKAT CANDUNG - R Fauzi (JCH (Jurnal Cendekia Hukum), 2019)
The purpose of this study was to find out and analyze the implementation of a criminal investigation of sexual intercourse and sexual abuse of children in the Fourth Admission Police Station. The method used in this research is empirical juridical research. The results showed that the research on the crime of intercourse and sexual abuse of children carried out by the investigating authority was in accordance with the provisions of the legislation. Investigation of this case is in accordance with the existing rules of receiving reports, confiscating evidence, arresting, detaining filing and sending files to the Public Prosecutor (P21). Factors inhibiting irregularities in the process of criminal acts of sexual intercourse and sexual abuse of children are: human resources from the investigator, victims are still children, the suspect does not argue, has nothing to do with seeing directly and does not want to come to provide assistance Information and bordering forensic doctors. The way out by investigators in the process of sexual intercourse and sexual abuse of children is to increase existing investigators and those requested by investigating members to the police station, allocate and request assistance to assist these sexual acts of sexual intercourse and coitus with the Social Service Bukittinggi, replace a lot of information and opinions will not come, then called back after it was visited at home to be able to provide information, the suspect did not confess then the investigator made a case at the location, processing evidence and multiply giving reports to provide information and help the doctor Forensics, the investigator is still waiting for the results of the post mortem.